2015
DOI: 10.1186/s12906-015-0959-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and protection against oxidative-induced damage of Acacia shaffneri and Acacia farnesiana pods extracts: in vitro and in vivo assays

Abstract: BackgroundObesity is a worldwide public health issue, reaching epidemic condition in developing countries associated to chronic diseases. Oxidative damage is another side effect of obesity. Antioxidant activity from plant components regulates at some extent this imbalance. Main goal of the present study was to determine the antioxidant activity and protection against oxidative-induced damage of Acacia shaffneri (AS) and Acacia farnesiana (AF) pods extracts.MethodsTo evaluated antioxidant activity and radical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…7- O -galloyl catechin, +catechin and methyl gallate are the main bioactive metabolites with anticancer potential against breast and prostate cancer [ 27 29 ]. Various species of genus Acacia were reported for their antioxidant and protective potentials against lung toxicity in animal models [ 31 ]. A. hydaspica AHE fraction showed significant hepato-protective potential against cisplatin persuaded hepatic damage in rats [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…7- O -galloyl catechin, +catechin and methyl gallate are the main bioactive metabolites with anticancer potential against breast and prostate cancer [ 27 29 ]. Various species of genus Acacia were reported for their antioxidant and protective potentials against lung toxicity in animal models [ 31 ]. A. hydaspica AHE fraction showed significant hepato-protective potential against cisplatin persuaded hepatic damage in rats [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioassay-guided isolation identified 7-O-galloyl catechin, catechin, catechin gallate, and methyl gallate as major antioxidant and anticancer phytoconstituents from A. hydaspica ethylacetate fraction (AHE) ( Afsar et al, 2016a , Afsar et al, 2018 , Afsar et al, 2016 ). Genus Acacia exposed antioxidant and nephroprotective proficiencies in animal prototypes ( Puga et al, 2015 ). The aqueous extract of A. Senegal showed significant nephroprotective potency against gentamicin (100 mg/kg) induced renal damage by lowering serum creatinine and urea levels in rats ( Mohammed, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was caused by cavitation during power ultrasound, causing molecules to produce ·OH, which in turn attacked Cy-3-glu, resulting in the lost ability of the latter to scavenge free radicals. Thus, the ability of Cy-3-glu to remove ·OH decreased [23,24]; the greater the intensity of power ultrasound, the more severe the damage would be.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the result of spectral analysis, the residual anthocyanins after power ultrasound remained to be in the form of salt cationic (AH + , red). The degradation products were not hydroxybenzoic acid, hydroxyl-benzaldehyde, and chalcone, so the antioxidant activity did not [22,23]. Turfan [19] found that the main mechanism of anthocyanin degradation by H 2 O 2 includes three reactions: ·OH generation and induction of the benzene of anthocyanins to generate CO 2 and H 2 O [24].…”
Section: Resultsmentioning
confidence: 99%